Tingkat Kepuasan Klien terhadap Pelaksanaan Sanitasi dan Hygiene pada SPA Homecare by Deby - Nuri Nur Hartini; Ifa Nurhayati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the level of client satisfaction regarding the implementation of sanitation and hygiene at SPA Homecare by Deby. Given the mobile nature of homecare services, the implementation of hygiene protocols is crucial for client safety. The method used in this study was a quantitative descriptive percentage approach. The subjects of this study included all clients who had received services at SPA Homecare by Deby, using a sampling technique known as accidental sampling. Data were collected through a 4-point Likert scale questionnaire distributed online and offline to clients aged 17-50 years. Data analysis was performed by calculating frequency percentages and achievement scores to determine assessment categories based on a range of 0%-100%. The findings of this study indicate that overall, the level of client satisfaction is in the